Exploring innovative growth of a music distribution software - CERVAK, HANNA; SKÖLD, LOVISA (My University, 2022)
Being independent enables Aspiring Artists to have full creative freedom, but for those who wish to make music a full-time career, dedication and effort is needed to overcome the struggle of becoming a professional. By recognizing such challenges, this master’s thesis was set out to investigate and conceptualize transformational innovation within the field of independent music distribution. By conducting qualitative user-based activities, such as interviews and a diary study, data on the topic could be gathered and compiled into user profiles, an emotional journey map and thematically pinpointed challenges. Moreover, forming trust, facilitating collaborations and conducting successful promotions was identified as the most challenging factors for Aspiring Artists. In addition, these insights were transformed into six concepts, which later arrived at one final concept through the use of evaluative research. The final concept, Facilitating Collaborations, allows artists to foster trust amongst each other in a safe environment, as a result improving social capital acquisition in that context. This can be achieved by forming the interface, as well as the collaborations, around the process of jointly building a traceable song that in a secure and controlled manner displays contributions. To conclude, the design presented aims to balance digital ownership, collaborations and social capital acquisition. When combining such perspectives with the area of interaction design, the researchers created a solid foundation for reaching transformational innovation both within the context of design and Aspiring Artists. To guide this development process, a list of requirements was created based on the insights gained. Arguably, when applied and evaluated in the final design, these can be used as design factors to consider when designing for transformational innovation in the context of Aspiring Artists.
Keywords: interaction design; user experience; emotions in design; trust in design; transformational innovation; social capital; independent music distribution; independent artists